Live imaging of paracrine signaling: Advances in visualization and tracking techniques - Eriko Deguchi; Michiyuki Matsuda; Kenta Terai (Cell Structure and Function)
Live imaging techniques have revolutionized our understanding of paracrine signaling, a crucial form of cell-to-cell communication in biological processes. This review examines recent advances in visualizing and tracking paracrine factors through four key stages: secretion from producing cells, diffusion through extracellular space, binding to target cells, and activation of intracellular signaling within target cells. Paracrine factor secretion can be directly visualized by fluorescent protein tagging to ligand, or indirectly by visualizing the cleavage of the transmembrane pro-ligands or plasma membrane fusion of endosomes comprising the paracrine factors. Diffusion of paracrine factors has been studied using techniques such as fluorescence correlation spectroscopy (FCS), fluorescence recovery after photobleaching (FRAP), fluorescence decay after photoactivation (FDAP), and single-molecule tracking. Binding of paracrine factors to target cells has been visualized through various biosensors, including GPCR-activation-based (GRAB) sensors and Förster resonance energy transfer (FRET) probes for receptor tyrosine kinases. Finally, activation of intracellular signaling is monitored within the target cells by biosensors for second messengers, transcription factors, and so on. In addition to the imaging tools, the review also highlights emerging optogenetic and chemogenetic tools for triggering the release of paracrine factors, which is essential for associating the paracrine factor secretion to biological outcomes during the bioimaging of paracrine factor signaling. Key words: paracrine signaling, live imaging, biosensors, optogenetics, chemogenetics